Training on the Basic Communication Development and Basic Teaching Skills at the 3rd Batch of Basic Instructional Technique Skills Improvement Training (PEKERTI) at the University of Bengkulu - Rosane Medriati; Lenni Mantili Hutauruk; Kashardi Kashardi (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2023)
This training aims to train lecturers in developing the basics of Communication and Basic Teaching Skills in PEKERTI (Basic Instructional Engineering Skills Improvement) Batch 3 2023 activities. The activity was carried out in May 2023 at the University of Bengkulu, with 53 participants in the training who were lecturers from the Singaperbangsa Karawang University College. The research instrument used was a closed questionnaire with four answer choices. The data analysis technique used is descriptive statistical analysis. PEKERTI participant response analysis related to training activities was carried out on the data obtained as a percentage. Percentages are obtained based on modified Likert Scale calculations. The research results show that almost 80% of the respondents were in the Strongly Agree category based on the guidelines in Table 4 of the Likert scale interpretation. Moreover, only one respondent is in disagree category. In other words, the respondents who were the sample in this study only gave answers that strongly agreed and agreed to the 52 positive statements submitted in the questionnaire developed regarding training on Basic Communication Development and Basic Teaching Skills at the 3rd Batch of Basic Instructional Technique Skills Improvement Training (PEKERTI) at the University of Bengkulu. In conclusion, the training for developing the Basics of Communication and Basic Teaching Skills in PEKERTI Batch 3 at the University of Bengkulu received a positive response from the participants.